Self-reported narcissistic traits in patients with addiction through the lens of the ICD-11 model for personality disorders - Riegel, Karel D.; Schlosserova, Lucia; Zbornik, Tadeas S. (Frontiers in Psychiatry, 2022)
Background: There is a presumption that pathological narcissism, or narcissistic personality disorder per se, can be considered a precursor to addiction. Although the ICD-11 model does not distinguish specific personality disorders, narcissistic psychopathology should be captured through personality trait qualifiers. Objectives: To verify the capacity of the ICD-11 model in the detection of narcissistic psychopathology in patients with addiction; to test its discrimination capacity, convergent validity, and specificity towards the gender and the type of addiction. Methods: Two samples were employed in the study. Sample 1 (n = 421) consisted of patients with addiction; Sample 2 (n = 567) consisted of general population volunteers. Age range was 18-75 years and a battery of self-assessment questionnaires containing Personality Inventory for DSM-5 – Brief Form Plus Modified; Triarchic Psychopathy Measure; Hypersensitive Narcissism Scale; and Level of Personality Functioning Scale-Self Report was administered by pencil-and-paper method. Results: The following was confirmed: 1. capacity of the ICD-11 model in relation to capture narcissistic pathology; 2. the differentiation capacity between the clinical and non-clinical population; 3. gender specificity in relation to grandiose and vulnerable narcissism; 4. the connection between the overall degree of impairment in personality functioning and most of trait qualifiers; 5. certain specifics of patients with addiction in relation to the type of addiction. Conclusions: Results support the empirical and clinical relevance of the ICD-11 model in capturing narcissistic pathology in addicted patients. Clinical implications concerning assessment and treatment in addiction settings, and certain limits regarding the Anankastia domain are discussed.